2015
DOI: 10.1007/s10549-015-3601-2
|View full text |Cite
|
Sign up to set email alerts
|

The readability of online breast cancer risk assessment tools

Abstract: Numerous breast cancer risk assessment tools that allow users to input personal risk information and obtain a personalized breast cancer risk estimate are available on the Internet. The goal of these tools is to increase screening awareness and identify modifiable health behaviors; however, the utility of this risk information is limited by the readability of the material. We undertook this study to assess the overall readability of breast cancer risk assessment tools and accompanying information, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…Our readability results are consistent with previous studies, which have found high readability levels for other breast cancer-related topics such as risk assessment and treatment. 20,65,75 Our results clearly highlight the need for more plain-language dissemination of research about environmental risk factors. 76 …”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Our readability results are consistent with previous studies, which have found high readability levels for other breast cancer-related topics such as risk assessment and treatment. 20,65,75 Our results clearly highlight the need for more plain-language dissemination of research about environmental risk factors. 76 …”
Section: Discussionmentioning
confidence: 63%
“…16 A major report recommendation was to identify effective strategies for communicating accurate and reliable breast cancer risk information to diverse audiences given that individuals possess different literacy and numeracy skills and may prefer different formats for receiving and responding to health-related information. 1719 Prior research has examined the format and readability of breast cancer risk assessment tools 20,21 , however, important research questions persist regarding messaging about the link between breast cancer and environmental exposures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncologists in this study favored print-based patient education materials that they could share directly with their patients in the clinic. Given variables seen to impact communication in our study and the high literacy demands of existing tools (M=12.1 grade) (Brewer et al, 2012; Cortez, Milbrandt, Kaphingst, James, & Colditz, 2015; Lipkus et al, 2010), intervention modalities that support patient comprehension, value clarification and perceived risk accuracy are needed (Brewer et al, 2009; Lea, Kaphingst, Bowen, Lipkus, & Hadley, 2011; Reyna, Nelson, Han, & Dieckmann, 2009). Additional novel techniques that could be useful in this context include the use of metaphor for communicating about molecular tumor testing and targeted treatments (Pinheiro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, these materials are effective only if children can read, understand and apply the information. Previous studies have determined that health education materials are often developed with very little attention on their suitability for the target population (Cortez, Milbrandt, Kaphingst, James, & Colditz, ; Garnweidner‐Holme, Dolvik, Frisvold, & Mosdol, ; Howe, Barnes, Estrada, & Godinez, ). The suitability of health education materials refers to the extent to which such materials can be thoroughly understood and accepted by readers, including learning stimulation and motivation (Okuhara, Ishikawa, Okada, & Kiuchi, ).…”
Section: Introductionmentioning
confidence: 99%